AIDS Treatment and Intrahousehold Resource Allocation: Children's Nutrition and Schooling in Kenya - Zivin, Joshua Graff; Thirumurthy, Harsha; Goldstein, Markus (2012)
The provision of antiretroviral medications is a central component of the response to HIV/AIDS and consumes substantial public resources from around the world, but little is known about this intervention's impact on the welfare of children in treated persons' households. Using longitudinal survey data from Kenya, we examine the relationship between the provision of treatment to adults and the schooling and nutrition outcomes of children in their households. Weekly hours of school attendance increase by over 20% within 6 months after treatment is initiated for the adult patient. We find some weak evidence that young children's short-term nutritional status also improves. These results suggest how intrahousehold allocations of time and resources may be altered in response to health improvements of adults.